PENGARUH LABEL HALAL DAN LABEL BPOM TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK PADA KONSUMEN MUSLIMAH DI KOTA PALEMBANG - Nabila Cahyani; Listiawati; Yusiresita Pajaria (CV. Cendikiawan Muda Sriwijaya, 2025)
This research aims to analyze the influence of halal labels and BPOM (Indonesian Food and Drug Authority) labels on purchasing decisions of cosmetic products among Muslim female consumers in Palembang City. The research method employed a quantitative approach with data collection through questionnaires distributed to 82 Muslim female cosmetic users in Palembang City. Data analysis was conducted using Structural Equation Modeling (SEM) based on variance through the Partial Least Square (Smart-PLS) approach. The results showed that halal labels have a positive and significant effect on purchasing decisions with a t-statistic value of 4.147 (>1.96) and p-value of 0.000 (<0.05). BPOM labels also demonstrated a positive and significant influence with a t-statistic value of 3.773 (>1.96) and p-value of 0.000 (<0.05). The research model has an R-square value of 0.663, indicating that halal label and BPOM label variables explain 66.3% of purchasing decisions, while the remaining 33.7% is explained by other variables outside the research model. The measurement model testing showed that all indicators have loading factor values above 0.7 and Average Variance Extracted (AVE) values above 0.5, demonstrating good convergent validity. The composite reliability and Cronbach's alpha values of each construct are above 0.7, indicating good reliability. This research indicates that Muslim female consumers in Palembang City consider product halal status and safety as important factors in making cosmetic purchasing decisions. This research provides practical implications for cosmetic manufacturers to pay attention to halal and BPOM certifications as effective marketing strategies when targeting Muslim female consumers.